Penggunaan Padlet dalam Mereviu Buku untuk Meningkatkan Literasi Siswa - Sri Handayani, Wulan (Jurnal Didaktika Pendidikan Dasar, 2022)
This research was conducted to determine the increasing of student literacy by using Padlet in reviewing books. This is because there are only a few students who want to read books, and they also don’t want students to make book reviews because the form of the review is the Y Chart, Ishikawa Fishbone and AIH Paragraph. Reading is a basic literacy that must be developed to master other literacy so that this literacy must be mastered well. This research conducted in class 6A the elementary School of 2 Kota Kulon as many as 29 students. The research approach used is a qualitative approach where data collection is done through interviews, observations, questionnaires, and documentation. Techniques and data analysis were carried out through data collection, data presentation, data reduction, and drawing conclusions. The results of the interview stated that Padlet is a medium that can improve student literacy. From the observations obtained data that the activity of student in literacy has increased. The conclusion of this research is that Padlet can improve student literacy in reviewing books.